Sisneros to head guard unit - Wildermuth, Todd (Raton Range Raton, New Mexico, 1994)
Newspaper Article on Gene Sisneros becoming the First Northern New Mexican to command the state's National Guard Air defense unit.
Master list item #: 18
File location is in the Raton File Cabinet
Keywords: Sisneros, Gene; Montano, Mel; Army Reserve National Guard; Director of Personnel and Administration; Raton High School; Local History; Biography; Life and Customs; National Guard; Brigade Troop; Military Career; Platoon Leader; Military Medal -- National Defense Service -- Armed Forces Reserve; Raton, New Mexico; Albuquerque, New Mexico; Santa Fe, New Mexico